Experimental Study of Turbine Mechanism Using Cantilever PVDF Piezoelectric with Current Power on a Laboratory Scale: Experimental Study of Turbine Mechanism Using Cantilever PVDF Piezoelectric with Current Power on a Laboratory Scale - Ede Mehta Wardhana; Adi Kurniawan; Alisyach Sukma Ridzky Ramdhany (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This research explores the integration of Internet of Things (IoT) technology with MEMS (Micro Electro Mechanical Systems) sensors and piezoelectric technology to enhance the efficiency and operational sustainability of devices. IoT connects physical devices to the internet to collect and exchange information and has become an integral part of Industry 4.0. The main components of IoT include physical objects, communication channels, software, operations, and data. In this study, IoT development focuses on the maritime sector with the application of MEMS sensors, piezoelectric technology, ocean current speed, and turbines. The use of piezoelectric technology allows devices to operate autonomously by harvesting energy from vibrations and pressure, further improving the efficiency of IoT devices. Experimental results show that in an open circuit, the highest average voltage at a speed of 1.1 m/s reached 0.019606 mV (capacitor) and 0.0056 mV (non-capacitor). In a closed circuit, with one non-capacitor piezoelectric, the average voltage was 14.762 mV and the average current was 0.0027 mA, producing a power output of 0.0398 mW. With four non-capacitor piezoelectrics, the average voltage reached 33.174 mV and the current was 0.0044 mA, producing a power output of 0.0146 mW. Meanwhile, with one capacitor piezoelectric, the average voltage was 4.947 mV and the current was 0.0023 mA, producing a power output of 0.01138 mW. With four capacitor piezoelectrics, the average voltage was 16.627 mV and the current was 0.0036 mA, producing a power output of 0.05986 mW. These results indicate that the piezoelectric turbine mechanism has significant potential as a reference for the development of future renewable energy technologies. The implementation of this technology allows IoT and MEMS devices to function autonomously and sustainably, supporting applications in various sectors including maritime and industry.